Pharmacological evaluation and validation for the folkloric use of Oligochaeta ramose in constipation and diarrhea - Musaddique Hussain; Shahid Masood Raza; Khalid Hussain Janbaz (Bangladesh Pharmacological Society, 2014)
Crude extract of Oligochaeta ramose and its fractions were studied to rationalize its traditional use in GIT disturbance. In spontaneous contracting jejunum preparation, O. ramose (0.01-1.0 mg/mL) caused a transient spasmogenic effect followed by the spasmolytic effect at higher doses (3.0-10.0 mg/mL). In atropinized jejunum preparation, O. ramose inhibit the spontaneous and K+ (80 mM)-induced contraction at the similar doses (0.01-1.0 mg/mL), suggesting calcium channel blocking effect. The calcium channel blocking effect was confirmed when pretreatment of tissue with O. ramose produced a dose-dependent shift in Ca+2 dose- response curve to the right, similar to that produced by the verapamil. Activity-directed fractionation revealed that the spasmolytic effect is concentrated in the dichloromethane fraction while, aqueous fraction contains both spasmogenic and spasmolytic constituents. This study validate the presence of both spasmogenic and spasmolytic components mediated through muscarinic receptor activation and calcium channel blockade respectively, which may explain its traditional uses in constipation and diarrhea.